Variations in bacterial pathogens causing early onset neonatal septicaemia, according to birth weights - a 5 year study in a referral hospital of West- Bengal (Bangladesh Journal of Medical Microbiology, 2012)
Bacterial sepsis continues to be a major cause of morbidity and mortality in neonates. The features of sepsis being non- specific, a high index of suspicion can only save a precious life. Pathogens of early onset septicaemia may vary, from one country to another and within a country from one place to the other. This study had been undertaken t o understand the variations in the pathogens of early onset neonatal septicaemia according to birth weights ,their susceptibility patterns to commonly used antibiotics in this age of emerging resistance and to utilise this data for better empirical treatment of this potentially fatal conditions. Blood samples from 255 babies belonging to various birth weights and of both sexes with definitive inclusion and exclusion criteria were processeed according to standard laboratory protocols during a five year period, from February 2005-2010, in a rural referral hospital of West Bengal. Culture positivity was found in 63/255 samples (24.70%), comprising of Klebsiella pneumoniae (31.74%) and methicillin sensitive Staphylococcus aureus (31.74%) as predominant isolates. Male: female ratio was 1.25:1. The susceptibility pattern of isolates has been discussed. It is observed that bacteriology of early onset neonatal septicaemia varies according to birth weights. In very low birth weight babies Eshcherichia coli is the predominant organism and culture positivity is highest (87.5%). Where as culture postivity in low birth weight and normal weight babies with sepsis are 32.89% and 29.26% respectively.In low birth weight babies Staphylococcus aureus and in normal weight babies Klebsiella pneumoniae are the predominant organisms. Birth weight of babies and development of neonatal sepsis are significantly associated x2= 7.174, p